Cultural Narratives and Heritage Tourism in the Digital Age: A Netnographic Study of the Royal Graves of Hadat Banggae, West Sulawesi - Firmansyah, Firmansyah; Akbar, Muh; Sonni, Alem Febri (Tuturlogi: Journal of Southeast Asian Communication, 2026)
This study analyzes the representation of the Royal Graves of the Hadat Banggae in Majene, West Sulawesi, within the digital sphere through a netnographic approach. The research focuses on cultural, historical, and religious narratives produced on YouTube, Instagram, and Facebook related to the site. Data were collected through passive-participant observation, documentation of visual and textual content, and analysis of audience comments. The findings reveal that each platform serves distinct functions: YouTube emphasizes documentation and education, Instagram highlights aesthetic and visual identity, while Facebook functions as a space for community interaction. The resulting cultural narratives encompass historical, symbolic, religious, aesthetic, educational, and participatory dimensions. Visual and textual analysis indicates that the representation of the graves is not limited to a traditional burial site but also constitutes a dynamic cultural construct, open to public interpretation, and functioning simultaneously as a heritage tourism destination. These findings underscore the role of digital media as a cultural mediation space that interweaves collective memory, local identity, and the consumption of historical tourism. The study highlights the importance of digital literacy, academic–community collaboration, and preservation strategies to ensure that cultural heritage continues to thrive within the digital communication landscape.